Rickettsia sibirica mongolitimonae Infections in Spain and Case Review of the Literature - Sonia Santibáñez; José Manuel Ramos-Rincón; Paula Santibáñez; Cristina Cervera-Acedo; Isabel Sanjoaquín; Encarnación Ramírez de Arellano; Sara Guillén; María del Carmen Lozano; Marta Llorente; Mario Puerta-Peña; Elena Aura Bularca; Alejandro González-Praetorius; et al. (Emerging Infectious Diseases)
Rickettsia sibirica mongolitimonae is an emerging cause of tickborne rickettsiosis. Since the bacterium was first documented as a human pathogen in 1996, a total of 69 patients with this infection have been reported in the literature. Because of the rising rate of R. sibirica mongolitimonae infection cases, we evaluated the epidemiologic and clinical features of 29 patients who had R. sibirica mongolitimonae infections confirmed during 2007–2024 at the Center for Rickettsiosis and Arthropod-Borne Diseases, the reference laboratory of San Pedro University Hospital–Center for Biomedical Research of La Rioja, Logroño, Spain. We also reviewed all cases published in the literature during 1996–2024, evaluating features of 94 cases of R. sibirica mongolitimonae infection (89 in Europe, 4 in Africa, and 1 in Asia). Clinicians should consider R. sibirica mongolitimonae as a potential causative agent of rickettsiosis, and doxycycline should be administered promptly to avoid clinical complications.